Inflammation Self‐Limiting Electrospun Fibrous Tape via Regional Immunity for Deep Soft Tissue Repair. Issue 39 (28th August 2022) - Saiding, Qimanguli; Cai, Zhengwei; Deng, Lianfu; Cui, Wenguo
Abstract: Overexpression of inflammatory cytokines and chemokines occurs at deep soft tissue injury sites impeding the inflammation self‐limiting and impairing the tissue remodeling process. Inspired by the electrostatically extracellular matrix (ECM) binding property of the inflammatory signals, an inflammation self‐limiting fibrous tape is designed by covalently modifying the thermosensitive methacrylated gelatin (GelMA) and negatively charged methacrylated heparin (HepMA) hydrogel mixture with proper ratio onto the electrospun fibrous membrane by mild alkali hydrolysis and carboxyl‐amino condensation reaction to restore inflammation self‐limiting and promote tissue repair via regional immunity regulation. While the GelMA guarantees cell compatibility, the negatively charged HepMA successfully adsorbs the inflammatory cytokines and chemokines by electrostatic interactions and inhibits immune cell migration in vitro. Furthermore, in vivo inflammation self‐limiting and regional immunity regulation efficacy is evaluated in a rat abdominal hernia model. Reduced local inflammatory cytokines and chemokines in the early stage and increased angiogenesis and ECM remodeling in the later phase confirm that the tape is an approach to maintain an optimal regional immune activation level after soft tissue injury. Overall, the reported electrospun fibrous tape will find its way into clinical transformation and solve the challenges of deep soft tissue injury. Abstract : Inspired by the electrostatically binding property of the inflammatory signals to extracellular matrix, an inflammation self‐limiting fibrous tape is designed by covalently modifying the thermosensitive methacrylated gelatin (GelMA) and negatively charged methacrylated heparin (HepMA) hydrogel onto the electrospun fibrous membrane by alkali hydrolysis and carboxyl‐amino condensation to restore inflammation self‐limiting and promote tissue repair.